Marketing Strategy Plan for Residential Land Plots at PT Prima Raya Property in Kudus Regency (Pusat Riset dan Inovasi Nasional, 2026)
This research was conducted to (1) Identify the internal and external environment, (2) To determine the strategic position of the SWOT matrix qualitatively, (3) To determine strategic steps. In the identification process, internal factors are identified using the 4P marketing mix theory (product, price, promotion, and place/distribution) , external factors using the Major External Forces theory , then the analysis uses SWOT by including various perspectives and categories that are considered relevant to describe the company's actual situation. To delve deeper into this discussion, the author used a descriptive qualitative research approach with the SWOT analysis technique as the primary tool for analyzing strengths, weaknesses, opportunities, and threats. Data collection was conducted through triangulation through direct observation, in-depth interviews, and literature review. review of supporting documents , as well as the author's experience in understanding marketing dynamics. This research also involves a number of parties who act as the main subjects. The subjects involved in this research include internal elements of the company. The results of this analysis are expected to be able to provide a comprehensive and accurate picture of the current state of the company, and can be a basis for reference in the preparation of medium and long-term strategies that are more focused, realistic, and adaptive to future marketing opportunities based on data and able to design more effective and competitive marketing strategies.